Extrapulmonary tuberculosis in surgical aspect- expanded challenging disease spectrum - Mohan, Manjul; Kumar, Amit; Kumar, Prabhod; Kumar, Pramod; Raza, Arshad (International Journal of Medical Research and Review, 2018)
Introduction: This study was designed to analyse wide spectrum magnitude of extra pulmonary tuberculosis in surgical aspect with its clinico-patho-radiological profile and treatment modalities. Material and Methods: The study was conducted in postgraduate Department of Surgery in collaboration with Department of Chest and Tuberculosis,Pathology and Radio diagnosis of Rohilkhand Medical College and Hospital Bareilly, Uttar Pradesh, India, after formal approval from institutional ethics committee. This study is of prospective study, in duration of January 2015 to April2018. Inclusion criteria: All suspected cases of extra pulmonary tuberculosis (EPTB). Exclusion Criteria: (1) HIV patients (2) Patients with pulmonary tuberculosis. Result: A total of 59 patients with suspected EPTB were included, investigated and treated with or without surgical intervention followed by standard ATT regimes. Pathological / Microbiological: FNAC, Histopathology, AFB insputum &CBNAAT, BACTEC 460, ADA. Radiological: X–Ray chest, X-ray abdomen.Ultra-Sonography (USG), Contrast Enhanced Computer Tomography (CECT). Patients admitted in emergency department and attending surgical out patient department were investigated and treated as per protocol. In our study 39 patients out of 59 underwent different surgical procedure and followed by antitubercular treatment regime. 20 Non-operated patients treated medically with antitubercular treatment regime [ATT]. Conclusion: EPTB has same national health issue as pulmonary tuberculosis. For tuberculosis control, EPTB-A challenging disease should be early diagnosed and surgically and medically treated to decrease related morbidity and mortality.